1991
DOI: 10.1007/bf00037077
|View full text |Cite
|
Sign up to set email alerts
|

Organ-specific expression of different histone H3 and H4 gene subfamilies in developing and adult maize

Abstract: The steady-state levels of H3 and H4 mRNAs transcribed from three H3 and two H4 multigene subfamilies were studied during germination and in different organs of maize. During germination the five subfamilies are expressed in parallel to DNA synthesis, but a 5-fold difference in the quantity of mRNAs transcribed per gene copy was found from our subfamily to another. In adult plants H3 and H4 mRNA levels are highest in organs containing meristematic tissues but also high in non-proliferating tissues. No strict t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…These results suggest that the expression of HMG2 could be restricted to tissues containing actively dividing cells. This assumption is supported by our results on the pattern of accumulation of HMG2 mRNA, which closely resembles that of histone H4 mRNA, which is known to be preferentially expressed in young tissues with high mitotic activity (37). While the broad expression of HMG1 suggests that it may encode a housekeeping form of HMGR, the enzyme encoded by HMG2 might have a more specialized role in the synthesis of specific isoprenoids required in actively dividing cells.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These results suggest that the expression of HMG2 could be restricted to tissues containing actively dividing cells. This assumption is supported by our results on the pattern of accumulation of HMG2 mRNA, which closely resembles that of histone H4 mRNA, which is known to be preferentially expressed in young tissues with high mitotic activity (37). While the broad expression of HMG1 suggests that it may encode a housekeeping form of HMGR, the enzyme encoded by HMG2 might have a more specialized role in the synthesis of specific isoprenoids required in actively dividing cells.…”
Section: Discussionsupporting
confidence: 78%
“…It is worth noting that the levels of HMG1 mRNA are much higher than those of HMG2 mRNA, which was detected only when poly(A)+ RNA was used. Since HMG2 mRNA was exclusively detected in parts of the plant containing meristematic tissues, the same mRNA samples were analyzed for the presence of histone H4 mRNA, known to be expressed in actively dividing cells (37). Fig.…”
Section: Materlils and Methodsmentioning
confidence: 99%
“…Northern analysis in various tissues of plants indicated that they are actively transcribed in tissues with high mitotic activity, suggesting that most of plant histone genes primarily belong to a class of replication-dependent histone genes [4,11,18,25]. However, these studies also demonstrated that histone mRNAs are detected at low levels in tissues that do not have division activities, suggesting that higher plants also carry replication-independent histone genes.…”
Section: Introductionmentioning
confidence: 73%
“…Chromatin structure and sensitivity to nucleases of the histone H3C4 gene promoter region Expression of the genes encoding histones progressively increases during the early steps of maize germination to reach a maximum after 4 days [5]. At that stage the concentration of histone mRNA in embryos is high, although they are present primarily in meristematic tissues, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The H3C4 gene which is studied here is a member of a small multigene subfamily of 4-5 copies. Its expression as well as that of the histone genes in general is under a strict regulatory control resulting in a preferential accumulation of specific mRNAs in proliferating tissues [5,13]. Evaluation of the activity of an Arabidopsis H4 promoter in transgenic plants strongly suggests the regulation to occur essentially at the level ofgene transcription [ 1 ], and the expression to result from both a low replication-independent and an enhanced replication-dependent activity [151.…”
Section: Introductionmentioning
confidence: 99%